Analisis Sistem Informasi Identitas Kependudukan Digital Disdukcapil Kota Samarinda Oleh Mahasiswa Universitas Muhammadiyah Kalimantan Timur - Muhammad Zaidan Nibroos; Syalika Ayu Wulandari; Indri Anzelina; Arbansyah Arbansyah (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
As of October 30, 2023, about 186,535 people living in Samarinda City must have a Citizenship Card (CTP), but only 11,525 people have a Digital Identity (IKD). Using the internship methods carried out by Muhammadiyah Kalimantan East University Computer Engineering students at the Samarinda Civil Registration and Population Service, this study investigates these differences. The research conducted observations, interviews, and document analysis to describe the challenges in the adoption of ICTs, including how effective the process was and the opinions of officials. The results provide students with a perspective on public IT and legal foundations and technical guidelines governing ICTs. The aim of this research is to help Disdukcapil improve administrative efficiency and increase public acceptance of digital identity technologies.